2006
DOI: 10.1029/2006gl026963
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐phase relative rates technique for measuring aerosol reaction kinetics

Abstract: [1] A mixed-phase relative rates approach for measuring rates of reaction in aerosols is presented. Using this method the rate of reaction of methyl oleate (MO) particles, normalized to the gas-particle collision rate, was measured to be g MO = 1.12 (±0.36) Â 10 À3 with 2-methyl-2-butene as the gas-phase reference. This value compares favorably with our previously published value of 1.23 Â 10 À3 measured using an absolute technique. Reaction of bis(2-ethylhexyl) sebacate (BES) particles with Cl and OH radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 30 publications
4
93
4
Order By: Relevance
“…In contrast, the latter case may lead to γ values that are greater than unity when secondary condensed-phase chemistry is an important loss mechanism for condensed-phase species. For example, Hearn and Smith (2006) measured γ 0 =2.0 for OH oxidation of BES particles, which is somewhat larger than our value. From their results, Hearn and Smith (2006) suggested that OH-initiated secondary chemistry lead to additional loss of BES.…”
Section: Kinetic Studiescontrasting
confidence: 49%
See 1 more Smart Citation
“…In contrast, the latter case may lead to γ values that are greater than unity when secondary condensed-phase chemistry is an important loss mechanism for condensed-phase species. For example, Hearn and Smith (2006) measured γ 0 =2.0 for OH oxidation of BES particles, which is somewhat larger than our value. From their results, Hearn and Smith (2006) suggested that OH-initiated secondary chemistry lead to additional loss of BES.…”
Section: Kinetic Studiescontrasting
confidence: 49%
“…Laboratory research has concentrated on the reaction of O 3 with condensed-phase unsaturated organic compounds, e.g., oleic acid, as a proxy for chemical aging of organic aerosol (e.g., Morris et al, 2002;Hearn and Smith, 2004;Katrib et al, 2004;Thornberry and Abbatt, 2004;Hearn and Smith, 2005;Katrib et al, 2005;Knopf et al, 2005;Ziemann, 2005). Fewer studies have been conducted to investigate the chemical aging of condensed-phase saturated organics by atmospheric radicals (e.g., Bertram et al, 2001;Moise and Rudich, 2001;Eliason et al, 2004;Molina et al, 2004;Hearn and Smith, 2006;Knopf et al, 2006;Hearn et al, 2007;Lambe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Typical values for the uptake of OH by saturated organic compounds are 0.3-1.0. 11,12,16,20,21 Because the primary reaction between OH and a hydrocarbon is the abstraction of an H atom, a very fast process, γ in this chemical system has been interpreted to mean that OH accommodates efficiently, i.e. nearly every OH collision results in an oxidation reaction, and therefore γ represents the overall accommodation process directly.…”
Section: Articlementioning
confidence: 99%
“…Other trace gases, such as OH and NO 3 , are also involved in important heterogeneous reactions (e.g. Bertram et al, 2001;Molina et al, 2004;Hearn and Smith, 2006;Knopf et al, 2006;Gross and Bertram, 2008;Park et al, 2008;Gross and Bertram, 2009), but have not been shown to adhere to Langmuir adsorption kinetics with subsequent surface reactions (Langmuir-Hinshelwood type reactions) and are therefore not the subject of this study. Although we attempt to use realistic values characteristic of an urban plume scenario as input parameters, our purpose is not to make exact atmospheric predictions.…”
Section: Introductionmentioning
confidence: 99%